Answer:
f(x) = -x³ + 3x² + 4x - 12
Step-by-step explanation:
f(x)=(x+2)(-x+3)(x-2)
Step 1. Use the difference of two squares
(x + 2)(x - 2) = x² - 4
f(x) = (-x + 3)(x² - 4)
Step 2. Long multiplication
x² - 4
<u>-x + 3 </u>
-x³ + 4x
<u> + 3x² - 12</u>
-x³ + 3x² + 4x - 12
f(x) = -x³ + 3x² + 4x - 12
Answer: the second option
explanation: below
I believe the answer would be 4!
So 4 * 3 * 2 * 1
24.
Here's proof :
ABCD
ABDC
ACBD
ACDB
ADBC
ADCB
BACD
BADC
BCAD
BCDA
BDAC
BDCA
Following this order, each letter has 6 additional options, so 4! Would answer this appropriately. Some would say 6*4 but that's the same as 4*3*2 (3 and 2 becomes 6)
Angle TVU = 1/2 (120 - 12) = 108/2 = 56°
Therefore, the correct answer is D.
Standard form is Ax + By = C
Where A is a positive integer
The y needs to be moved to the left side so subtract 3y from both sides.
2x - 3y = -8